2022
DOI: 10.1111/nbu.12540
|View full text |Cite
|
Sign up to set email alerts
|

Association between vegetarian and vegan diets and depression: A systematic review

Abstract: Recent evidence suggests that vegetarian and vegan diets may increase the risk and symptoms of depression, a mental health condition affecting 350 million people globally. We aimed to systematically review the literature on the associations between vegetarian and/or vegan diets and the risk or symptoms of depression using evidence from both observational and intervention studies. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, with pre-specification of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 85 publications
(192 reference statements)
0
15
2
Order By: Relevance
“…Notably variation in the classification of diet types, sampling population and small effect sizes may have contributed to outcomes. 7,8,10 Instead, we observed that neuroticism predicted only anxiety and stress outcomes. As…”
Section: Personality Traits and Mental Outcomescontrasting
confidence: 65%
“…Notably variation in the classification of diet types, sampling population and small effect sizes may have contributed to outcomes. 7,8,10 Instead, we observed that neuroticism predicted only anxiety and stress outcomes. As…”
Section: Personality Traits and Mental Outcomescontrasting
confidence: 65%
“…Devoid of vital nutrients like vitamin B12 and omega-3 fatty acids that are necessary for brain function, vegan diets could be associated with depression. Despite having potential advantages like lower rates of obesity, diabetes, heart disease, and cancer, some studies claim that individuals on vegetarian/vegan diets had a higher risk of depression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a higher percentage of the study population belonged to the rural class, which might be attributed to the fact that 1/3rd of the Indian population resides in rural areas and is associated with factors such slow education, poverty, and environmental factor adversities. Finally, a higher proportion of the subjects were nonvegetarian; the observation conflicted with the published studies, which conclude that vegetarian diets are associated with a higher risk of depression [ 17 ].…”
Section: Discussionmentioning
confidence: 84%